Eduardo Archetti. - Archetti, Eduardo (CLACSO, 2017)
Eduardo Archetti has been one of the best known and appreciated anthropologists in Latin America. This is a compilation of his work. Deserved tribute from CLACSO, from his colleagues and friends to a great Latin American intellectual. Born in Santiago del Estero, Argentina, he studied sociology in Buenos Aires and later completed his doctoral studies in France. He was a professor at the University of Oslo, FLACSO in Buenos Aires, and directed the Rural Development Graduate Program at CLACSO in Quito, among many other activities and responsibilities. His work is multiple and we have divided it into four moments, which were often simultaneous or overlapped in time. In the first part of this book we consign rural and peasant studies. Archetti was a precursor and an unavoidable reference in agrarian studies and on the peasantry in Latin America.